MAP Kinase-Interacting Kinase 1 Promotes Proliferation and Invasion of Hepatocellular Carcinoma and Is an Unfavorable Prognostic Biomarker - Wang, Xujing (Med Sci Monit, 2018)
BACKGROUND: Hepatocellular carcinoma (HCC) accounts for one of the most prevalent tumor types in the world. The MAP kinase-interacting kinase 1 (MNK1) functions downstream of MAP kinases such as p38 and ERK, and its potential role in cancer development is being uncovered. The aim of this study was to investigate the expression and function of MNK1 in HCC. MATERIAL/METHODS: Immunohistochemical staining and quantitative PCR were performed to explore the expression of MNK1 in both HCC tissues and adjacent normal liver tissues. Chi-square test, univariate analysis, and multivariate analysis were conducted to statistically evaluate clinical significance of MNK1 in HCC. Proliferation, migration, and invasion capacities of HCC cells were assessed after overexpressing or silencing MNK1. RESULTS: Both the RNA and protein levels of MNK1 were upregulated in HCC tissues compared to normal liver tissues. High expression of MNK1 was correlated with advanced tumor stage and poor overall survival. Moreover, MNK1 was identified as a novel independent prognostic factor for HCC patients. Cellular studies showed that MNK1 can enhance the proliferation, migration, and invasion capacities of HCC cells, thereby promoting tumor progression. CONCLUSIONS: High expression of MNK1 is frequent in HCC tissues, which promotes tumor proliferation and invasion, and is correlated with a poor overall survival. Targeting MNK1 may be a novel direction for the drug development of HCC therapy.